Antimicrobial copper nanoparticles synthesized from waste printed circuit boards using advanced chemical technology. (August 2018) - Tatariants, Maksym; Yousef, Samy; Sakalauskaitė, Sandra; Daugelavičius, Rimantas; Denafas, Gintaras; Bendikiene, Regita
Graphical abstract: Highlights: Chemical and ultrasonic treatment were used to recover Cu from WPCBs. Advanced chemical was employed to synthesize Cu-NPs from recovered metal. The Cu-NPs had the average size of 7 nm with yield ∼90 wt% and final purity 97%. The obtained Cu-NPs showed good antimicrobial activity. The Cu-NPs production price was ∼6 times lower than the commercial cost of Cu-NPs. Abstract: Waste Printed Circuit Boards (WPCBs) were classified as one of the most important resources for urban mining containing high purity Copper (Cu) and other valuable materials. Recently, a dissolution recycling approach enhanced by ultrasonic treatment succeeded in the liberation of Cu foils from WPCBs as received. This research aims to synthesize Copper Nanoparticles (Cu-NPs) from the recovered Cu by using an advanced chemistry approach to obtain nano-product with high added value taking into consideration environmental risks. The experiments were carried out on the Cu foils recovered from the three types of WPCBs with different purity of Cu (Motherboard, Video Card, and Random Access Memory (RAM)). The synthesis process was performed in two stages: (a) preparation of Copper (II) Sulfate aqueous solutions from the recovered Cu and (b) chemical reduction of solutions for synthesis of Cu-NPs by using Native Cyclodextrins (NCDs), particularly ß-NCD as stabilizers. The efficiency of the developed approach for raw material of different purity was assessed and the final yield and the estimated recovery cost of synthesized Cu-NPs were calculated with high accuracy as well as the properties of the synthesized Cu-NPs. The obtained Cu-NPs were examined using SEM-EDS, TEM, XRD, Raman Spectroscopy, and TGA. To maximize the potential biomedical application benefits, the antibacterial activity of Cu-NPs was investigated by the standard microdilution method for E. coli, P. aeruginosa, and S. aureus bacterial cultures. The results showed that the produced Cu-NPs had an average size of 7 nm and yield 90%, while the preparation costs were 6 times lower in comparison to the commercial counterparts. In addition, the results indicated that the synthesized Cu-NPs from RAM sample had a good antimicrobial action.